2001
DOI: 10.1073/pnas.111455498
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of and phylogenetic relationships among living amphibians

Abstract: The phylogenetic relationships among the three orders of modern amphibians (Caudata, Gymnophiona, and Anura) have been estimated based on both morphological and molecular evidence. Most morphological and paleontological studies of living and fossil amphibians support the hypothesis that salamanders and frogs are sister lineages (the Batrachia hypothesis) and that caecilians are more distantly related. Previous interpretations of molecular data based on nuclear and mitochondrial rRNA sequences suggested that sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 50 publications
2
63
0
4
Order By: Relevance
“…5A) (Cao et al 2000). The phylogenetic analyses (with MP, NJ, and ML) of a molecular data set which included complete mitochondrial protein-coding, rRNA, and tRNA genes further supported the phylogenetic position of turtles as sister group of archosaurs (crocodiles+birds) (Zardoya and Meyer 2001) (Fig. 5B).…”
Section: Mitochondrial Evidencementioning
confidence: 90%
See 1 more Smart Citation
“…5A) (Cao et al 2000). The phylogenetic analyses (with MP, NJ, and ML) of a molecular data set which included complete mitochondrial protein-coding, rRNA, and tRNA genes further supported the phylogenetic position of turtles as sister group of archosaurs (crocodiles+birds) (Zardoya and Meyer 2001) (Fig. 5B).…”
Section: Mitochondrial Evidencementioning
confidence: 90%
“…C Turtles have diapsid affinities, and are the sister group of Archosauria (e.g. Kumazawa and Nishida 1999;Zardoya and Meyer 2001). D Turtles have diapsid affinities, and are the sister group of Lepidosauria (e.g.…”
mentioning
confidence: 99%
“…Paradoxically, some distributional patterns and some data from the fossil record (Estes and Wake 1972;Estes and Reig 1973;Rage and Rocek 1989;Jenkins and Walsh 1993;Duellman and Trueb 1994;Evans et al 1996;Evans and Borsuk-Bialynicka 1998;Rocek 2000) point at an initial divergence of living amphibians much earlier than the Mesozoic continental fragmentation of the Pangaea supercontinent. Moreover, alternative molecular phylogenies based on complete mitochondrial genomes (Zardoya and Meyer 2001;San Mauro et al 2004) support the "Batrachia" hypothesis ( ). Anura ϩ Caudata In order to test whether lissamphibian splits were triggered by Mesozoic continental breakup events, and to distinguish among competing hypotheses, we reconstructed a robust molecular phylogeny based on the RAG1 gene, encompassing for the first time a wide taxon sampling of major lissamphibian lineages.…”
mentioning
confidence: 95%
“…The Lissamphibia are widely thought to be a monophyletic group, constituted by three monophyletic orders (Anura, Caudata, and Gymnophiona) whose origin and interrelationships remain hotly debated (see Meyer and Zardoya 2003 for a recent review). The poor fossil record of some major lissamphibian groups and the fact that the three living amphibian orders possibly acquired their specialized morphology very early in their evolutionary histories (Zardoya and Meyer 2001) have left many questions unresolved regarding the origins, relationships, and historical distribution of the Lissamphibia.A recent molecular phylogeny of lissamphibians based on mitochondrial rRNA genes grouped salamanders and caecilians to the exclusion of frogs and suggested that the early evolutionary history of living amphibians was associated with the Mesozoic continental fragmentation of the supercontinent Pangaea (Feller and Hedges 1998). Paradoxically, some distributional patterns and some data from the fossil record (Estes and Wake 1972;Estes and Reig 1973;Rage and Rocek 1989;Jenkins and Walsh 1993;Duellman and Trueb 1994;Evans et al 1996;Evans and Borsuk-Bialynicka 1998;Rocek 2000) point at an initial divergence of living amphibians much earlier than the Mesozoic continental fragmentation of the Pangaea supercontinent.…”
mentioning
confidence: 99%
See 1 more Smart Citation